Log-linear approaches to lag-sequential analysis when consecutive codes may and cannot repeat. [article]. - Hilton, Denis J.
G. P. Sackett's (1979) lag-sequential analysis is recast in log-linear terms. Differing from articles by P. D. Allison and J. K. Liker (see record 1982-12033-001) and by D. Iacobucci and S. Wasserman (see record 1989-14205-001), sequences that, for logical reasons, do not allow consecutive events to be assigned the same code are considered. In addition, overlapped sampling, which the sequential analysis literature usually assumes, is contrasted with nonoverlapped sampling of sequences, which is also used and may seem more faithful to some statistical models. Several advantages of a log-linear approach to sequential problems are noted, including its ability to deal routinely with the structural zeros created when consecutive codes cannot repeat and its integration of sequential methods into an established and well supported statistical tradition. -- (from the author)